THE USE OF LIQUID SMOKE AS LATEX COAGULANT FOR RUBBER FARMER GROUP IN BUKIT LITI VILLAGE, CENTRAL KALIMANTAN - Lilis Rosmainar; Karelius; Rasidah; I Nyoman Sudyana; Nyahu Rumbang; Idam Sulastri (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
Bukit Liti Village is one of villages located in the Kahayan Tengah Sub-district, Pulang Pisau Regency, Central Kalimantan Province. Most people there tap rubber tree simply managed to produce bokar (rubber materials). In making bokar, rubber farmers use coagulant materials that can damage the rubber quality and soak bokar in water pool/creeks which lower the rubber quality and produce bad smell. To solve the problem, a training is conducted to make a simple pyrolysis reactor to produce liquid smoke which will be used as latex coagulant preventing and reducing bad smell and improving the bokar quality. Pyrolysis reactor is made from a used oil tank, and other materials with a thermometer to measure reactor temperature. The reactor is designed to allow a minimum oxygen combustion. The production of rubber wood liquid smoke for latex coagulation process in this research with 50 kg of old rubber wood materials has obtained 125 ml liquid smoke for 4-hour production time. The use of liquid smoke as latex coagulant gives real impacts for farmers such as: environmental friendly, to prevent bacterial growth and oxidation in the latex and latex lump, to prevent and reduce bad smells of bokar from the plantation, during storage and rubber processing in the rubber processing factory. The technology advantages of the liquid smoke are: faster coagulation, high elasticity, able to increase dry rubber content, relatively same price with other coagulant, to increase quality and selling price, produce clean latex and free of environment pollutant.